THE ROLE OF THE AUDIT COMMITTEE IN MODERATING THE EFFECT OF EARNINGS MANAGEMENT AND TAX AVOIDANCE ON COMPANY VALUE - Dade Nurdiniah; Lucia Ari Diyani (Universitas Agung Podomoro, 2022)
This study aims to determine the role of the audit committee in moderating the effect of earnings management and tax avoidance on firm value. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange, while the research sample is manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The sample selection technique used purposive sampling, the number of research samples was 28 and the number of observations of research data obtained was 140. This study used multiple linear regression and moderated regression analysis with a random effects model approach. The results of this study indicate that earnings management has a negative effect on firm value, while tax avoidance as proxied by the cash effective tax rate has no effect on firm value. Then the audit committee does not moderate the effect of earnings management on firm value, as well as the audit committee does not moderate the effect of tax avoidance on firm value.